2008
DOI: 10.1055/s-2008-1081333
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Transcript Profiling Reveals Down-Regulation of A Sterol Pathway Relevant Gene and Overexpression of Artemisinin Biogenetic Genes in TransgenicArtemisia annuaPlants

Abstract: To investigate the dynamic fluctuation of terpenoid relevant transcriptomics in transgenic ARTEMISIA ANNUA plants that express the genomic integrated antisense squalene synthase gene ( ASSS), we have quantified the transcript levels of the sterol anabolic SS gene as well as artemisinin biogenetic amorphadiene synthase (ADS), cytochrome P450 monooxygenase (CYP71AV1) and cytochrome P450 reductase (CPR) genes by real-time fluorescent quantitative polymerase chain reaction (RFQ-PCR). The SS mRNA level in transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 22 publications
6
25
0
Order By: Relevance
“…Direct measurement of 1 O2 burst from chilling and senescent leaves has provided strong support to an involvement of 1 O2 in the non-enzymatic conversion to artemisinin, but whether artemisinin biosynthesis genes are also inducible under the stress circumstance that triggers 1 O2 emission remains unclear. In the context of senescence and chilling, it was observed that 1 O2 burst from chilled and senescent leaves can really induces artemisinin biosynthesis genes, reiterating that 1 O2 is a common signal that modulate artemisinin accumulation either in senescent A. annua leaves or after A. annua leaves acclimatized to chilling (Feng et al 2008;Zeng et al 2008b).…”
Section: Glandular Trichomes Are Dominant Sites Storing Artemisininmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct measurement of 1 O2 burst from chilling and senescent leaves has provided strong support to an involvement of 1 O2 in the non-enzymatic conversion to artemisinin, but whether artemisinin biosynthesis genes are also inducible under the stress circumstance that triggers 1 O2 emission remains unclear. In the context of senescence and chilling, it was observed that 1 O2 burst from chilled and senescent leaves can really induces artemisinin biosynthesis genes, reiterating that 1 O2 is a common signal that modulate artemisinin accumulation either in senescent A. annua leaves or after A. annua leaves acclimatized to chilling (Feng et al 2008;Zeng et al 2008b).…”
Section: Glandular Trichomes Are Dominant Sites Storing Artemisininmentioning
confidence: 99%
“…Although artemisinin production was reported to be influenced by natural stress (Chen and Zhang 1987;Martinez and Staba 1988;Ferreira et al 1995), no direct evidence indicating the involvement of 1 O2 in artemisinin biosynthesis has been provided for many years. Feng et al (2008) The sustained release of 1 O2 is recognized from a gradual decline of absorbance at 440 nm (A440) due to the bleaching of the selective 1 O2 acceptor N, N-dimethyl-p-nitrosoaniline.…”
Section: Glandular Trichomes Are Dominant Sites Storing Artemisininmentioning
confidence: 99%
See 2 more Smart Citations
“…7). Researchers have reported that a co-suppression phenomenon can often occur in overexpressing transgenic plants (Yang et al, 2008;Banyai et al, 2010).…”
Section: Expression Of Aaics1 In Transgenic Plantsmentioning
confidence: 99%